Comparing cardiac MRI and lung PET/CT after completion of tuberculosis treatment – preliminary findings of participants co-enrolled into the StatinTB trial and Cardiac Imaging After TB (CIA-TB) study. (3rd October 2022) - Mukasa, S; Aremu, O; Wolmarans, K; Mashinyira, A; Katoto, P; Jakoet-Bassier, F; Kotze, T; Samuels, P; Jaftha, M; Maishi, P; Guler, R; Ntusi, N; et al.
Abstract: Introduction: Mortality rates after successful tuberculosis (TB) treatment remain elevated and healthy survival is impaired by chronic pulmonary disease and persistent inflammation. Inflammation leads to a complex cascade of events and has been associated with cardiovascular disease (CVD). Recent epidemiological work described an increased risk of CVD in persons with history of TB. Aims and objectives: In our ongoing StatinTB trial (NCT04147286), we evaluate safety and efficacy of 40 mg atorvastatin to reduce persistent lung inflammation (PLI) after TB treatment in HIV−/HIV+ adults measured by 18F-FDG-PET/CT. Participants are co-enrolled into the Cardiac Imaging After Tuberculosis (CIA-TB) study. Here we report preliminary findings of participants enrolled into the StatinTB trial and CIA-TB study with the aim to correlate PLI with cardiac magnetic resonance imaging (CMR) parameters. Methods: Participants with clinical response to TB treatment and a negative sputum culture at 16 weeks were screened at the end of a 24-week course of treatment for drug-sensitive TB. PET/CT was performed on a Philips Gemini TF scanner and analysed using MIM®Software. PLI was defined as total lung glycolysis (TLG) ≥50 SUV·mL (Figure 1). CMR was performed using a 3T Siemens Magnetom Skyra scanner and parameters were derived from the following acquisitions: SSFP cine imaging of the short and long axes, T1 mapping (MOLLI, 5 (3) 3), T2 mapping and late gadolinium enhancement (LGE) imaging. StatinTB trial is conducted according to ICH-GCP. Results: 26 participants (mean age 37.8±13.8 years, 38.5% women) underwent PET/CT and CMR. 23.1% were infected with HIV, 34.6% smokers, and 26.9% had a previous history of TB. Median BMI was 21.3 (IQR 19.7; 24.3). One participant reported hypertension. Common symptoms at enrollment were cough (26.9%), shortness of breath (11.5%), and chest pain (3.9%). On CT scan, 73.1% had pulmonary nodules, 57.7% scarring, 50.0% cavities, 42.3% bronchiectasis, 19.2% centrilobular disease, 19.2% distorted lung architecture, and 11.5% consolidations. On PET/CT, PLI was detected among 11 (42.3%) participants with a mean TLG of 216.0 (IQR 78.2; 384.0). In a multivariable regression analysis, left ventricular end systolic volume (LVESV) (−1.46; 95% CI: −2.89, −0.23; p=0.047) and distorted lung architecture (2.84; 95% CI: 1.17, 4.52; p=0.003) were significantly associated with TLG. Native T1 relaxation time showed a strong, but not significant association with TLG (15.01; 95% CI: −8.08, 38.10; p=184). Conclusion: We present data of a young cohort at the end of TB treatment without significant cardiac risk factors. Structural lung disease is affecting at least half of participants, and many remain symptomatic. PLI is present in more than one-third of participants and our preliminary findings suggest an association with cardiac impairment. Further enrolment and ongoing laboratory studies will shed more light into post-TB cardio-pulmonary sequelae. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): EDCTP